2020
DOI: 10.3390/ijms21020530
|View full text |Cite
|
Sign up to set email alerts
|

Components from the Human c-myb Transcriptional Regulation System Reactivate Epigenetically Repressed Transgenes

Abstract: A persistent challenge for mammalian cell engineering is the undesirable epigenetic silencing of transgenes. Foreign DNA can be incorporated into closed chromatin before and after it has been integrated into a host cell’s genome. To identify elements that mitigate epigenetic silencing, we tested components from the c-myb and NF-kB transcriptional regulation systems in transiently transfected DNA and at chromosomally integrated transgenes in PC-3 and HEK 293 cells. DNA binding sites for MYB (c-myb) placed upstr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 101 publications
(144 reference statements)
0
1
0
Order By: Relevance
“…For instance, we have demonstrated that adding NF-Y and MYB transcriptional activator target DNA sequences upstream of a minimal promoter increased luciferase expression from transfected pDNA in prostate cancer PC-3 cells. [6,7] Fusion proteins can also be used as transgene-specific regulators to boost expression in mammalian cells. [8][9][10][11] Both approaches, enhancer elements and fusion protein regulators, require the addition of DNA target sequences into the pDNA, which may not always be possible or desirable.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, we have demonstrated that adding NF-Y and MYB transcriptional activator target DNA sequences upstream of a minimal promoter increased luciferase expression from transfected pDNA in prostate cancer PC-3 cells. [6,7] Fusion proteins can also be used as transgene-specific regulators to boost expression in mammalian cells. [8][9][10][11] Both approaches, enhancer elements and fusion protein regulators, require the addition of DNA target sequences into the pDNA, which may not always be possible or desirable.…”
Section: Introductionmentioning
confidence: 99%